madisonmaruhnich94
Solve the equation. 78 = -2 (m+3) + m
Delete
Share
This Question is Closed
dfresenius
Best Response
You've already chosen the best response.
0
ok distribute the -2 to the m + 3
Nameless
Best Response
You've already chosen the best response.
0
first distribute the -2 so 78 = -2m + 6 + m. then combine like terms. so 78 = m + 6. then isolate the variableby subtracting 6 from both sides, thus m = 72
madisonmaruhnich94
Best Response
You've already chosen the best response.
1
wouldnt it be -72?
dfresenius
Best Response
You've already chosen the best response.
0
you would get 78 = -2m - 6 + m
dfresenius
Best Response
You've already chosen the best response.
0
-2m + m = -m
Yahoo!
Best Response
You've already chosen the best response.
0
-39 = 2m + 3
-42 = 2m
m = -21
madisonmaruhnich94
Best Response
You've already chosen the best response.
1
A. –28
B. –42
C. –72
D. –84
dfresenius
Best Response
You've already chosen the best response.
0
78 = -m - 6
dfresenius
Best Response
You've already chosen the best response.
0
72=-m
dfresenius
Best Response
You've already chosen the best response.
0
m= - 72
dfresenius
Best Response
You've already chosen the best response.
0
-72 is the right answer, they must have read your question wrong